Mother's satisfaction with the existing labor and delivery care services at public health facilities in West Shewa zone, Oromia region, Ethiopia - Gizachew Abdissa Bulto; Dereje Bayissa Demissie; Tefera Likasa Tasu; Getu Alemu Demisse (BMC, 2020)
Abstract Background Mothers' satisfaction with care during childbirth is indicators of the quality care which affects skilled birth attendance. Negative client's experiences at health facilities cause them to delay or avoid seeking care, which highlights services providers should consider and act on the expectations and experiences of women and their families. Though there are few studies conducted in Ethiopia on maternal satisfaction with Labor and Delivery (LAD) services, there is no study conducted in the study area. Therefore the study aims to assess the mother's satisfaction with existing LAD services and associated factors at all levels of health care in the West Shewa zone. Methods An institution-based cross-sectional study was conducted at public health facilities in West Shewa zone, Central Ethiopia. A systematic sampling technique was used to select 560 respondents by using their delivery registration number and data were collected through face to face interview. Mothers were considered satisfied if they responded satisfied/very satisfied with 75% or more of the questions assessing satisfaction. Binary and multivariable logistic regression analysis was used to identify associated factors. Results The overall proportion of mothers who were satisfied with the current LAD care services were 60.8%. The main areas of dissatisfaction were; accessibility and cleanness of toilets/shower 72.6%, overall cleanness of the facility/including waiting-area 40.1% and presence of support a person during birth 38.0%. The presence of cultural practices (AOR = 2.5), discussion on the place of delivery with health worker during ANC (AOR = 1.75), providers asks for consent before procedure (AOR = 2.77), encouraging companion to remain with mother (AOR = 2.22), never leave mother alone or unattended (AOR = 2.56), giving periodic updates on status and progress of labor (AOR = 2.04) and explaining what is being done and to expect during LAD (AOR = 2.20) were factors identified to be significantly associated with satisfaction on LAD services. Conclusion The overall satisfaction of mothers with LAD services at public health facilities in the West-Shewa zone was relatively low. Presence of cultural practices, discussion on the place of delivery, asking for consent before the procedure, encouraging companion to remain with mothers and explaining what is being done were factors identified. Therefore, all stakeholders have to emphatically work on those identified factors to improve mothers' satisfaction with LAD services.